Thickness Effect on Some Physical Properties of the Ag Thin Films Prepared by Thermal Evaporation Technique - Mohammed Ahmed Mohammed (Journal of Global Pharma Technology, 2018)
Silver (Ag) "thin films were successfully deposited by thermal evaporation using Edward’s Auto 306 Magnetron Sputtering System"(homemade). Theirstructural, optical and electrical properties were investigatedby using XRD, AFM, SEM, UV-Vis, electrical conductivity and the Hall effect, respectively. The average grain size increased from 20.03nm to 51.86 nm with increasing thin film thickness. The deposited Ag thin films had an absorbance ranging between 0.21-0.1, the values of energy gap were obtained in the range of 3.2-2.0 eV.Keywords Thermal evaporation, Thickness of thin film, Ag films, Hall effect, X-ray diffraction.